PEMBELAJARAN AGAMA TEMATIK UNTUK PENDIDIKAN PEMBEBASAN - Atiqullah, Atiqullah (Institut Agama Islam Negeri Madura)
AbstractThis paper emphasizes that moral action is the most intelligent action in a civilization which is obtained through educational efforts that expand the potential, interests, and talents of students, because the essence of the humanization of education goals and conscious. Thematic learning on themes that required the students so that learning in the educational unit organized in an interactive, inspiring, fun, challenging, motivating learners to actively participate and provide enough space for innovation, creativity and independence in order to liberate and emancipate protege from the fetters of verbal culture, authoritarian culture of the deadly power of human creativity. Kata-kata kuncipendidikan, tujuan pembelajaran, pembelajaran tematik